Futenvol: an innovative game for physical education students - Jay Carlo S. Bagayas; Chiedel Joan San Diego; Sotero O. Malayao Jr.; Griffter A. Sumando (Intelektual Pustaka Media Utama, 2026)
Teaching sports without sufficient equipment and facilities is a perennial challenge for physical educators in the Philippines. This study aimed to develop sports innovation targeting dual purpose of addressing facility scarcity while developing specific skill. This involved students (n=327) students enrolled in bachelor of physical education (BPEd) program and service physical education courses. Through a research and development design, the developmental process followed the analyze, design, develop, implement, and evaluate (ADDIE) model with the prime consideration of developing functional body coordination at the lower extremities such as ball control, kicking power, and kicking accuracy. These are vital for futsal and football with smaller play area requirement. The name Futenvol comes from the skills to be developed from futsal and football, while using the volleyball rotations and the rally of tennis, thus the coined name Futenvol. Repeated trial plays covering three iterative versions on court layout, game mechanics, and actual play resulted to the optimal version and showed that the innovation is highly acceptable. Above all, it is proven to develop flexibility and explosiveness in lower extremities that are basic skill-related components of fitness. The innovated game can be used as practice game while the exact court layout is not yet available thus greatly leveraging skills acquisition despite facility scarcity.